A framework to build readers and writers in the second language classroom - Zúñiga Camacho, Gilma (Colombian Applied Linguistics Journal, 2003)
This article proposes a framework to create readers and writers in the second language classroom. The components of the framework are curriculum, instruction and assessment. The curriculum states the goals and philosophy of the program that intends to create lifelong readers that find reading as a source of entertainment and information. It will also include the kind of literacy that the curriculum wants to support, the effect of reading in the first language, and the use of appropriate materials to achieve the goals. Instruction is framed under principles like reading is thinking and learning, reading and writing are taught together, and technology influences reading and writing development. Assessing reading in the second language classroom is the next component of the framework discussed in the article and it proposes the use of authentic tools like portfolios and observations. Traditional tools like tests are also mentioned.